A import??ncia do direito do petr??leo para administra????o p??blica sob a ??tica do novo marco regulat??rio: uma estatal para o pr??-sal - Guimar??es Neto, Napole??o Lopes (2016)
This is the context of the importance of establishing a new regulatory framework for the exploration and production of oil and natural gas reserves in the area of pre-salt layer, through constitutional confrontation of various doctrinal and jurisprudential understandings. In this sense, the central legal aspect of this work consists in the performance of the monopoly activities assured the Union considering the need to establish a new state company for that specific purpose.